Structural transformation and sources of growth in Turkey - Ahmet Ihsan Kaya; Cumhur Çiçekçi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper provides a comprehensive analysis of the supply and demand side of structural transformation in Turkey. Using the GGDC/UNU-WIDER Economic Transformation Database, we find that labour productivity improvements explain more than half of economic growth in the period 1980-2021. This is mainly thanks to within-sector productivity improvements, while the contribution of structural change declines over time. Time-series regression analysis shows that structural change is driven by per capita income growth and financial openness but is halted by trade integration. Furthermore, decomposition analysis from input- output tables demonstrates that domestic final demand has been the main source of output growth since 1980 and the contribution of export expansion has increased over time, but import dependency has persisted. The intermediate goods industry stands out as the locomotive sector in the economy throughout the entire period according to forward and backward linkage analysis.
Keywords: C67; O11; O47; J24; 330; labour productivity; structural transformation; economic growth; input-output; forward linkage; backward linkage